Pengaruh Perawatan Luka Menggunakan Madu terhadap Kolonisasi Bakteri Staphylococcus Aureus pada Luka Diabetik Pasien Diabetes Mellitus di Wilayah Kerja Puskesmas Rambipuji Kabupaten Jember (The Effect of Wound Care Using Honey on Staphylococcus Aureus Bac - Nuril Hudha Al Anshori; Nur Widayati; Anisah Ardiana (Pustaka Kesehatan, 2014)
Diabetic wound very easily causes complications in the form of infection caused by bacterialinvasion, and hyperglycemia condition boosts the growth of bacteria. One of the bacteria thatcan cause infection in diabetic wound is Staphylococcus aureus. Diabetic wound care can bedone with honey. Honey contains antibacterial, antioxidant and hydrogen peroxide that can killharmful germs. The purpose of this research was to identify the effect of wound care with honeyon Staphylococcus aureus colonization in diabetic wound. The research design used was a preexperimentwith one group pretest and posttest design. Sample was taken using consecutivesampling with 7 respondents. Data analysis applied dependent t-test and obtained p value of0.000 (p value <α = 0.05); it can be concluded that there is an effect of wound care with honeyon Staphylococcus aureus bacterial colonization in diabetic wounds of patients with DiabetesMellitus in work area of Public Health Center of Rambipuji Jember. The suggestion from thisstudy is to apply honey as a wound care agent because it has antibacterial activity that can helpprevent infection and accelerate wound healing.Keywords: wound care, diabetic wound, honey, Staphylococcus aureus